Impacto socioeconómico derivado de los créditos otorgados por la Corporación Grameen en el cantón Loja, período 2019-2023 - López Yunga, María del Cisne (2024)
Microcredit as a financial tool improves the quality of life of people who do not have access to resources through traditional financial services; one of the main beneficiaries are women, who, in this way, can make independent economic decisions; likewise, this type of credit stimulates different economic activities in different environments, directly empowering the partners of the institution that granted the credit and indirectly favouring families by reducing inequality of opportunities. Thus, the general objective of this research is to evaluate the socio-economic impact of the credits granted by the Grameen Corporation in the Loja canton, period 2019- 2023. The methodology applied followed a mixed descriptive, correlational and explanatory approach. In the descriptive part, 186 members who received microcredits in the years determined in the research were surveyed. Next, for the correlational and explanatory part, the Ordered Logit econometric model was used to determine the level of change in the lives of the members. The results indicate that 80,60 % of the beneficiaries already had an economic activity and thanks to the microcredit, they have managed to improve the quality of the product. However, 19,40 % of the funds were used to cover personal expenses, such as health, education, housing, debt repayment, which is considered an improper use of credit. The application of the econometric model reveals that the socio-economic impact reaches a medium level of change. Therefore, it is concluded that Grameen Corporation, through the granting of credit, has contributed significantly to improving the standard of living of its members, facilitating the growth of their small businesses and increasing their income.